2017
DOI: 10.1016/j.physbeh.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced obesity alters memory consolidation in female rats

Abstract: Obesity is a multifactorial disease characterized by the abnormal or excessive fat accumulation, which is caused by an energy imbalance between consumed and expended calories. Obesity leads to an inflammatory response that may result in peripheral and central metabolic changes, including insulin and leptin resistance. Insulin and leptin resistance have been associated with metabolic and cognitive dysfunctions. Obesity and some neurodegenerative diseases that lead to dementia affect mainly women. However, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 57 publications
2
12
1
1
Order By: Relevance
“…In our present study, neither selegiline treatment nor HFS diet‐induced moderate obesity had significant effects on motor activity or recognition memory. Although previous articles showed that extreme obesity induced cognitive dysfunction (Wang et al ., ; Zanini et al ., ), these changes could not be observed in our model of moderate obesity.…”
Section: Discussioncontrasting
confidence: 58%
“…In our present study, neither selegiline treatment nor HFS diet‐induced moderate obesity had significant effects on motor activity or recognition memory. Although previous articles showed that extreme obesity induced cognitive dysfunction (Wang et al ., ; Zanini et al ., ), these changes could not be observed in our model of moderate obesity.…”
Section: Discussioncontrasting
confidence: 58%
“…Neuroimaging studies have shown that hippocampal volume is diminished with aberrant neural activity in obese individuals compared to lean healthy individuals [ 48 , 49 , 50 ], indicating a potential mechanistic link between hippocampal function and metabolic health. Consistent with these results, rodent studies indicate that diet-induced obesity (via HFD or high-sucrose diet) manifests impaired memory consolidation [ 51 , 52 , 53 ] that is associated with hippocampal BBB disruption [ 54 , 55 ], thereby potentially increasing the entry of systemic inflammatory mediators into the hippocampus. Indeed, diet-induced obese animals exhibit microglial activation, increased production of ROS, and pro-inflammatory cytokines including IL-1β and TNF-α in the hippocampus [ 54 , 55 ].…”
Section: Mitochondrial Dysfunction In the Cnsmentioning
confidence: 71%
“…Accordingly, we found Ovx rats gained more than twice as much weight compared to Sham animals over the 10-week experiment. Excessive BW is a risk factor for mood disorders (Rocca et al 2009) and cognitive impairment (Zanini et al 2017) in humans and animals (Zanini et al 2017). However, it has been difficult to tease apart BW gain from ovarian hormone loss in the mechanisms contributing to Ovx-induced neurocognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The NOR test was adapted from Drumond et al and Zanini et al (Drumond et al 2012;Zanini et al 2017). This test uses the same apparatus and software (EthoVision XT; Noldus Information Technology) as for the OF test.…”
Section: Novel Object Recognitionmentioning
confidence: 99%